Molecular systematics and biology of two closely related blowflies : Lucilia sericata and Lucilia cuprina - Williams, Kirstin Alexa (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2015)
The greenbottle blowflies, Lucilia sericata (Meigen, 1826) and Lucilia cuprina (Wiedemann, 1830) (Diptera: Calliphoridae) are very difficult to distinguish on the basis of their external morphology. The literature suggests that these two species may be interbreeding. Sequencing two nuclear (28S rRNA and Period) and one mitochondrial (COI) gene indicated that there has been an ancient hybridization event and that mtDNA of L. sericata has become fixed in a lineage of L. cuprina through mtDNA introgression, possibly involving Wolbachia infection. This has implications for identifications of these species based on mtDNA alone. No study has shown explicitly that hybrids of L. sericata and L. cuprina can be identified morphologically. Morphological characters used to identify L. sericata and L. cuprina were scored and tested using specimens of both species and known hybrids. Discriminant function analysis of the characters successfully separated the specimens into three unambiguous groups "“ L. sericata, L. cuprina and hybrids. This is the first evidence that hybrids of these two species can be identified from physical characteristics.Lucilia sericata and L. cuprina have medical, veterinary and forensic importance. Knowing their distribution in South Africa would allow more effective management and utilisation of these flies. Their predicted geographic distributions in South Africa were modelled using maximum entropy analysis of selected climatic variables. The most important environmental variables in modelling their distributions were magnitude of monthly rainfall and the magnitude of the monthly maximum temperature for L. sericata, and the seasonal variation in monthly mean humidity and magnitude of monthly rainfall for L. cuprina. Both species have a widespread distribution in South Africa and one therefore cannot identify specimens of these flies by locality of capture alone.Luciliinae is a diverse and geographically widespread subfamily containing four genera - Hemipyrellia, Lucilia, Dyscritomyia and Hypopygiopsis "“ that all contain parasitic species ranging from saprophages to obligate parasites. The phylogenetic relationships between these genera are unclear. The 28S rRNA, COI and Period genes of 14 species of Lucilia and Hemipyrellia were partially sequenced and analysed together with 11sequences from GenBank and the Barcode of Life Database (BOLD). Lucilia sericata and L. cuprina were shown to be sister-species. Three cases of paraphylly were identified within Lucilia that affects identification of these species using mtDNA alone. Hemipyrellia consistently caused Lucilia to be paraphyletic when it was included in analyses, so Hemipyrellia should be synonymized with Lucilia. The relationships of Dyscritomyia and Hypopygiopsis to Lucilia are unclear and further studies are required. No geographic pattern was found within the different forms of parasitism within this group, but the different degrees of parasitism were phylogenetically clustered.
Keywords: Lucilia sericata; Lucilia cuprina